Analisis Potensi Shalegas Formasi Tanjung Cekungan Barito, Kalimantan Selatan Menggunakan Data Petrografi, SEM, Geokimia, XRD, dan Seismik 2D - Farizi, Faisal (Geological Engineering E-Journal, 2013)
The worlds needs for oil and gas continues to increase with the progression of human development and the number continues to increase. However, existing reserves may not be reliable in the future if there is no discovery of new reserves or expansion into the area of unconventional reserve. One of the Indonesian governments policy is to increase exploration and production of non-conventional oil and gas reserves such as shale gas to get large amounts of gas reserves. There are several formations that have been targeted in shalegas exploration in Indonesia. This research focus at Tanjung Formation as object. Tanjung formation has about 100 meters thick of shale and buried more than at a depth of 2000 meters. This research aim for identify potential of shale gas at Tanjung Formation which located in the basin Barito, South Kalimantan.Research methods used include survey methods, descriptive methods, and methods of analysis. In this study we used the analysis of petrographic, geochemical, SEM (scanning electron microscopy), XRD for surface samples and analysis of 2D seismic for dasubsurface data. In this study, we did integration surface and subsurface data. Surface sample from surface data is used to analog subsurface sample in tanjung formation to make a history of burial model. Petrographyc analysis show main porosity is dissolution and fracture, main organic material is fragmental and streak. SEM show mineral that have conviguration to creat microporosity, that minerals are illite and pyrite. XRD analysis show main mineral compose Tanjung shale is quartz (42-79%) and BI (Brittleness Index) value betwen 0,6-0,83. Based on Maturation history modeling of pseudowell-1 is known that the generation of hydrocarbons (gas) starts at 8 million years ago at a depth of 15 000 feet. Based on ambrose equation, Recoverable resources gas at tanjung shale is 18,425 TCF.